2007
DOI: 10.1021/ja071281e
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the Monoclinic to Cubic Phase Transition in the Fast Oxygen Ion Conductor La2Mo2O9 (LAMOX)

Abstract: La 2 Mo 2 O 9 (LAMOX) is a fast oxygen ion conductor which shows high oxygen ion conductivities comparable to those of yttria-sabilized zirconia (YSZ) . LAMOX is subject to a structural phase transition from the non-conductive monoclinic form to the highly-conductive cubic form at about 580°C. The origin of the conductivity in cubic LAMOX has been suggested to be due to a "disorder" in the O sub-lattice without any insight into the real distribution of the oxygen ion. In this paper, thanks to the application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
64
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 14 publications
2
64
0
Order By: Relevance
“…[4] Recently, some work has been devoted to the study of the static/dynamic nature of oxide ions in La 2 Mo 2 O 9 by molecular dynamics simulations [5,6] and by atomic pair distribution function analysis. [7] A drawback in the use of molybdates in SOFCs is the possibility that they will get reduced under low oxygen pressure. It has been previously shown that substitution of molybdenum by tungsten is likely to stabilize LAMOX compounds under reducing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Recently, some work has been devoted to the study of the static/dynamic nature of oxide ions in La 2 Mo 2 O 9 by molecular dynamics simulations [5,6] and by atomic pair distribution function analysis. [7] A drawback in the use of molybdates in SOFCs is the possibility that they will get reduced under low oxygen pressure. It has been previously shown that substitution of molybdenum by tungsten is likely to stabilize LAMOX compounds under reducing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The material, despite its simple chemical formula, has a remarkable 312 crystallographically unique atoms and is thus one of the most complex oxide structure reported to date. Our recent paper [13] based on a neutron PDF analysis of pure La 2 Mo 2 O 9 below and above the phase transition has highlighted the fact that the transition from the monoclinic to the cubic phase is a transition from a static to a dynamic distribution of the oxygen defects while preserving the monoclinic local structure. This agrees with the observation by Evans and co-authors that the b form of La 2 Mo 2 O 9 corresponds to a time-averaged version of the room-temperature structure, which has given an important input for the comprehension of the mechanism of oxygen diffusion in b-La 2 Mo 2 O 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Since blood group O individuals are not more likely to be infected, the main suspect is major virulence factor of Vibrio cholerae,the Cholera toxin (CT).Here, we present results showing that both El Tor and classical cholera toxin B-pentamers indeed bind blood group determinants (with equal affinities), using Surface Plasmon Resonance and NMR spectroscopy [1]. Taken together with our previous crystallographic data for CTB variants in complex with a blood group A analog [2,3], a picture emerges as to the molecular basis of cholera blood group dependence. [1] Heggelund The knowledge of the structural properties of crystalline materials is one of the most essential piece of information we need to obtain in order to make reliable correlations with physical properties, especially in functional materials.…”
mentioning
confidence: 52%
“…We should stress that, with respect to other classes of materials, the application of the PDF technique to materials for energetics is more recent. However, such new approach already showed its power in order to provide information at the atomic scale level that are essential to give new insights, for example, about the mechanisms involved in the carrier motion, study the defects structure and find correlations between different crystal structure of a material [3][4][5][6][7][8]. Examples will cover new oxide ion conductors such as La 2 Mo 2 O 9 , Ge-apatites, Ga-based melilites and Ba-indates.…”
mentioning
confidence: 99%